Smart Tree Media: Solusi Kreatif dalam Menguatkan Akhlak Terpuji Siswa - Zahwa, Randira Naja; Supriadi, Udin; Faqihuddin, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore the effectiveness of Smart Tree Media in increasing the understanding and practice of commendable morals in class V students at SD Al-Hidayah Ciumbuleuit. Using qualitative methods, through participatory observation and in-depth interviews with 10 students, it was found that the use of Smart Tree Media was successful in increasing learning motivation and helping students understand and apply commendable moral values ​​in everyday life. Smart Tree Media is in line with the principles of constructivism, Kohlberg's theory, and social constructivism, which involves students actively in learning. Students become more enthusiastic in discussing, sharing opinions, and relating theory to real experience, increasing their understanding. In addition, this method motivates students to express creativity and personal experiences in visual form, deepening their understanding of good morals. Smart Tree Media also helps develop critical, reflective and creative thinking skills. In conclusion, Smart Tree Media has great potential to increase students' understanding of good morals, although further research is needed to determine its long-term impact on students' character.